Tracking Intracavernously Injected Adipose-Derived Stem Cells to Bone Marrow - Lin, Guiting (2011)
Intracavernous (IC) injection of stem cells (SCs) has been shown to improve erectile function in various erectile dysfunction (ED) animal models. However, the tissue distribution of the injected cells remains unknown. In this study we tracked IC injected adipose-derived stem cells (ADSCs) in various tissues. Rat paratesticular fat was processed for ADSC isolation and culture. The animals were then subject to cavernous nerve (CN) crush injury or sham operation, followed by IC injection of one million autologous or allogeneic ADSCs that were labeled with 5-ethynyl-2-deoxyuridine (EdU). Another group of rats received IC injection of EdU-labeled allogeneic penile smooth muscle cells (PSMCs). At 2 and 7 days post-injection, penises and femoral bone marrow were processed for histological analyses. Whole femoral bone marrows were also analyzed for EdU-positive cells by flow cytometry. The results show that ADSCs exited the penis within days of IC injection and migrated preferentially to bone marrow. Allogenicity did not affect ADSC's bone marrow appearance either at 2 or 7 days, while CN injury reduced the number of ADSCs in bone marrow significantly at 7 but not 2 days. The significance of these results in relation to SC therapy for ED is discussed.